Why Do Cities Hoard Cash? Determinants and Implications of Municipal Cash Holdings - Gore, Angela K. (The Accounting Review, 2009)
ABSTRACT: This study examines the determinants of municipal cash holdings and the implications of holding high levels of cash. The first part of the analysis investigates municipal manager incentives to accumulate cash as part of normal operations. Results indicate that municipalities with a higher variation in revenues, fewer sources of revenues, and higher growth accumulate more cash. Larger governments and those receiving relatively more state revenue accumulate less cash. Further analysis considers whether high levels of cash indicate agency problems, and finds municipalities with high cash holdings spend more on administrative expenses, city manager salaries, and bonuses. I find no evidence that municipalities with excess cash reduce taxes. The presence of staggered councils and councils that are not independent tend to exacerbate excessive cash holdings. These results are consistent with the proposition that municipalities with high cash levels have agency problems relative to those with lower cash holdings.